Transient receptor potential vanilloid 4 channels are important regulators of parenchymal arteriole dilation and cognitive function. (22nd February 2019) - Diaz‐Otero, Janice M.; Yen, Ting‐Chieh; Ahmad, Amna; Laimon‐Thomson, Erinn; Abolibdeh, Bana; Kelly, Kara; Lewis, Matthew T.; Wiseman, Robert W.; Jackson, William F.; Dorrance, Anne M.
Abstract: Objective: Hypertension‐associated PA dysfunction reduces cerebral perfusion and impairs cognition. This is associated with impaired TRPV4‐mediated PA dilation; therefore, we tested the hypothesis that TRPV4 channels are important regulators of cerebral perfusion, PA structure and dilation, and cognition. Methods: Ten‐ to twelve‐month‐old male TRPV4 knockout (WKY‐ Trpv4 em4Mcwi ) and age‐matched control WKY rats were studied. Cerebral perfusion was measured by MRI with arterial spin labeling. PA structure and function were assessed using pressure myography and cognitive function using the novel object recognition test. Results: Cerebral perfusion was reduced in the WKY‐ Trpv4 em4Mcwi rats. This was not a result of PA remodeling because TRPV4 deletion did not change PA structure. TRPV4 deletion did not change PA myogenic tone development, but PAs from the WKY‐ Trpv4 em4Mcwi rats had severely blunted endothelium‐dependent dilation. The WKY‐ Trpv4 em4Mcwi rats had impaired cognitive function and exhibited depressive‐like behavior. The WKY‐ Trpv4 em4Mcwi rats also had increased microglia activation, and increased mRNA expression of GFAP and tumor necrosis factor alpha suggesting increased inflammation. Conclusion: Our data indicate that TRPV4 channels play a critical role in cerebral perfusion, PA dilation, cognition, and inflammation. Impaired TRPV4 function in diseases such as hypertension may increase the risk of the development of vascular dementia.